Resonant Axisymmetric Modes. Issue 1 (February 2021) - Porcelli, F; Yolbarsop, A; Barberis, T; Fitzpatrick, R
Abstract: Axisymmetric modes in shaped tokamak plasmas are normally associated with vertical displacement events. However, not enough attention has been given to the fact that these modes can be resonant in two different ways. Firstly, for a plasma bounded by a divertor separatrix, a generic n=0 ideal-MHD perturbation, ξ, is singular at the divertor X-point(s), where Beq · ∇ξ = 0, with Beq the equilibrium magnetic field. As a consequence, n=0 perturbations can give rise to current sheets localized along the divertor separatrix. Secondly, a feedback-stabilized n=0 mode tends to acquire an Alfvénic oscillation frequency. As a result, a resonant interaction with energetic particle orbits can lead to a new type of fast ion instability.